The planar limit of integrated 4-point functions - Bartomeu Fiol; Ziwen Kong (Journal of High Energy Physics, 2023)
Abstract We study the planar limit of integrated 4-point functions of moment map operators of 𝒩 = 2 SU(N) SQCD. We do so by considering the planar free energy on S 4 of the massive deformation of this theory, and taking advantage of the exact relation between this free energy and the integrated 4-point function. For this planar free energy we derive all the terms with maximal and next-to-maximal transcendentality, and present a procedure to compute terms of lower transcendentality. We also derive the first non-planar corrections, as all order series in the ’t Hooft coupling, and to all orders in transcendentality. Finally, we also apply our approach to the better studied example of 𝒩 = 4 SU(N) SYM integrated 4-point functions, and reproduce their known planar limit.